Comparison of Descemet Stripping Automated Endothelial Keratoplasty and Penetrating Keratoplasty in a Patient with Fuchs Endothelial Dystrophy - Alime Güneş; Kansu Tahir Bozkurt; Anıl Kubaloğlu (Türk Oftalmoloji Dergisi, 2013)
To report a patient with Fuchs endothelial dystrophy (FED) who underwent Descemet stripping automated endothelial keratoplasty (DSAEK) on one eye and penetrating keratoplasty (PK) on the fellow eye. A 74-year-old female patient with diagnosis of FED underwent uncomplicated cataract surgeries of both eyes, but developed bullous keratopathy eventually. The right eye underwent DSAEK and the left eye underwent PK. After 3 years of follow-up, the right eye had an uncorrected visual acuity (UCVA) of 20/40 and best-corrected visual acuity (BCVA) of 20/20 with spectacle correction (+2.25(-0.50x20°). Graft was clear with endothelial cell density (ECD) of 1532 cells/mm2 (donor ECD was 3215 cells/mm2) and central corneal thickness (CCT) was 674 µm. After 1 year of follow-up, the left eye had UCVA of 20/200, spectacle corrected (-3.50x100°) visual acuity of 20/125, and BCVA of 20/40 with rigid contact lens correction. Graft was also clear with ECD of 1785 cells/mm2 (donor ECD was 3100 cells/mm2) and CCT was 610 : This case report represents the advantages and disadvantages of two surgical techniques (PK and DASEK) applied on fellow eyes of a patient with FED (Turk J Ophthalmol 2013; 43: 202-4)